Individual Entrepreneurship in the Context of Diversity and Flexibility of Workplaces - Aleksandra Kulpa-Puczyńska (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
In the presented text, entrepreneurship is considered in the context of different ways of transforming the space of interpersonal relations and changes occurring in the organization of professional work associated, inter alia, with an individual and more flexible approach of the youngest generation of employees to the place of employment. The above trend is manifested by e.g. professional activity performed in today's popular coworking spaces, designed for the purpose of creative interactions and building contact networks, which are also crucial in the process of establishing an own business. The main purposes of the study involve: 1. a critical analysis of knowledge about flexible, innovative forms of work organization; 2. identification of the characteristics of flexible workplaces (from the point of view of contemporary employees), their positive and negative traits, relevant also for young entrepreneurs; 3. recognition of types and possibilities of professional activities performed (also by educators) in creative, customized workplaces. Hence, the research problems are clustered, inter alia, around the following question: Are the characteristics of the so-called flexible workplaces relevant for the youngest generation of potential and existing entrepreneurs – and if so, which of them? The project involves preliminary, qualitative research with the use, inter alia, of narrative interviews conducted with the use of thematically oriented cards with interview instructions, carried out among final-year students. The study takes into account the differences in professional experience of respondents, correspondingly to the variables of speciality and mode of study. The results of the theoretical analysis, complemented with the results of own research and professional experience may be useful for beginner entrepreneurs and entities supporting young people in coping with the competitive environment and the changing labour market. The abovementioned results also lead to the following conclusions: the formation of flexible and diverse work spaces (including the offering of interactive tools, opportunities to establish different professional relationships) gives employees, particularly young people, a lot of place to decide how and where to work. They can also spot opportunities associated with working on their own account and create a favorable working environment.
Keywords: 650; coworking spaces; diversity; flexibility of workplaces; young entrepreneurs